2007
DOI: 10.1007/s00383-007-1976-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic liver biopsy using cup-shaped punch biopsy forceps and argon beam coagulator in children

Abstract: Needle liver biopsy is insufficient for measuring enzyme activity in liver tissue in child cases of intrahepatic cholestasis because the biopsy specimen obtained is too small. This study was undertaken to validate the feasibility of a new, relatively non-invasive laparoscopic liver biopsy technique combining the use of laparoscopic cup-shaped punch biopsy forceps (CPBF) and an argon beam coagulator (ABC) handpiece for the diagnosis and examination of liver enzyme activity in cases of intrahepatic cholestasis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…A number of successful cases in the use of ABC have been reported [105109]. Dowling et al [110] reported that the ABC was more effective in management of spleenic trauma compared to traditional techniques(topical surgical, electrocautery, suture-ligation, digital pressure) in a study on ten adult pigs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of successful cases in the use of ABC have been reported [105109]. Dowling et al [110] reported that the ABC was more effective in management of spleenic trauma compared to traditional techniques(topical surgical, electrocautery, suture-ligation, digital pressure) in a study on ten adult pigs.…”
Section: Methodsmentioning
confidence: 99%
“…Most effective form of hemostasis and is used in procedures involving major blood loss [92, 105, 109]. …”
Section: Tablementioning
confidence: 99%
“…Следующим эта-пом проводят осмотр левой доли печени, селезенки, желудка. В последнюю очередь оценивают состояние органов малого таза (толстой кишки, аппендикса, мат-ки, фаллопиевых труб и яичников, грыжевых отверстий) [32]. Прицельного внимания требуют сосуды большого сальника, серозной оболочки желудка и париетальной брюшины, круглой и серповидной связок, расширение и извитой характер которых служат признаками разви-тия портальной гипертензии.…”
Section: лапароскопическая биопсияunclassified
“…However, the invasive method is expensive and risks serious complications such as bleeding and infection. Sampling error in LB can also lead to an unreliable diagnosis ( Okada et al, 2007 ; Patel & Sebastiani, 2020 ). TE is a non-invasive technique used to evaluate liver cirrhosis, but its results are associated with many factors, such as elevated aminotransferase or bilirubin levels, ascites, and extrahepatic cholestasis ( Millonig et al, 2008 ; Yan et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%